Investment Behavior by American Railroads, 1897-1914: A Comment - Morgan, W. Douglas (The Review of Economics and Statistics, 1971)
Economic historians should thank Larry Neal for his careful revision of the United States railroad investment series for the period between 1897 and 1914 [5]. However, the second major part of his article concerning the determinants of investmenit behavior over this period suffers from deficiencies of interpretation and requires further analysis which is the object of this note. Neal's thesis is that financial models, incorporating interest rates and cash flow variables, better explain railroad investment expenditures over this period than crude acceleration type mechanisms. In fact, he argues the time period 1897 to 1914 logically can be divided into two periods at the year 1907. In the earlier period (1897-1907) Neal argues that both easy access to external funds and the better use of internal funds are the primary explanations for investment behavior, while this was not the case after 1907. This thesis directly contradicts the earlier discussion of railroad investment made by Jan Kmenta and Jeffrey Williamson (K-W) [4]. The K-XV hypothesis purports that external costs were not important during this period and some sort of acceleration mechanism can best explain investment behavior. It is demonstrated below that the dominant determinant of long run railroad investment behavior over this period is the acceleration principle as asserted by K-W but that outside (as opposed to Neal's inside) financial conditions (the demand for financial instruments) contributed to the cyclical fluctuations of investment expenditures in the period prior to 1907.